Island in the city : a memoir - McCrary, Micah (American lives., 2018)
What forges the unique human personality? In Island in the City Micah McCrary, taking his genetic inheritance as immutable, considers the role geography has played in shaping who he is. Place often leaves indelible marks: the badges of self-discovery; the scars from adversity and hardship; the gilded stamps from personal triumphs; the tattoos of memory; and the new appendages--friendships, experiences, and baggage--we carry with us. Each place, with its own personality, has the power to form or revise our personhood in surprising and fascinating ways. McCrary considers three places he has called home (Normal, Illinois; Chicago; and Prague) and reflects on how these surroundings have shaped him. His sharp-eyed, charming memoir-in-essays contemplates how aspects of his identity, such as being black, male, middle-class, queer, and American, have developed and been influenced by where he hangs his hat.